Low-complexity approximation of 8-point discrete cosine transform for image compression - Puchała, Dariusz; Stokfiszewski, Kamil (Wydawnictwo Politechniki Łódzkiej, 2012)
In this paper the authors propose a new low-complexity approximation of 8-point discrete cosine transform (DCT) that requires 18 additions and two bit-shift operations. It is shown that the proposed transform outperforms significantly the known transform of the same computational complexity when applied to a JPEG compression stream in practical cases of encoding and decoding of still images. As such, the proposed transform can be effectively used in any practical applications where significant limitations exist regarding the computational capabilities coding and / or decoding devices, i.e. mobile devices or industrial imaging devices.